Implementing the Module and Learning Video in Turning Tapered to Enhance the Students’ Competency in Mechanical Engineering Education - Sarwi Asri; Ting Ting Wu; Muhammad Fariz Nasrullah Kamal (Faculty of Engineering, Universitas Negeri Yogyakarta, 2025)
The rapid advancements in technology and the demands of Industry 4.0 have underscored the need for innovative teaching approaches in Technical and Vocational Education and Training (TVET) to enhance students' practical competencies. This study evaluates the effectiveness of module-based and video learning in improving students' competencies in tapered turning within a lathe machining practice course. Employing a quasi-experimental design, the study involved 41 students from a Mechanical Engineering Education program, divided into an experimental group (19 students) and a control group (22 students). The experimental group used module-based and video learning tools, while the control group relied on traditional teaching methods. The findings revealed a statistically significant improvement in the experimental group's post-test scores compared to the control group (ð‘¡ = 8.59, ð‘ < 0.05), with a mean difference of 14.467. The experimental group also achieved an average normalized gain (N-Gain) score of 0.7063, categorized as